Relationships among social support, coping style, self‐stigma, and quality of life in patients with diabetic foot ulcer: A multicentre, cross‐sectional study. Issue 3 (8th August 2022) - Luo, Ruzhen; Ji, Yunan; Liu, Yan‐hui; Sun, Hongyu; Tang, Siyuan; Li, Xuechun
Abstract: Patients with diabetic foot ulcer have a significantly lower quality of life. Quality of life could be connected to other psychological or social processes. The purpose of this study was to examine the relationships between social support, decision regret, self‐stigma, and quality of life in patients with diabetic foot ulcers. The sample of the study consisted of 229 diabetic foot ulcer patients. Data were collected from September 2019 to March 2020. The demographic and clinical information, the Stigma Scale for Chronic Illness, Medical Coping Scale, Social Support Scale, and Quality of Life scale were used to assess the quality life for diabetic foot ulcer. Pearson correlation coefficient and structural equation modelling were used for data analysis. The quality of life was negatively correlated with self‐stigma, positively correlated with social support, giving up coping, and not significantly correlated with confrontation coping and avoidance coping. Self‐stigma has significant indirect effects on quality of life through social support and coping style. Further clinical intervention strategies for decreasing self‐stigma as well as strengthening social support and positive coping styles are needed to inform diabetic foot ulcer patients, thus improving their quality of life.